EBG Size Reduction for Low Permittivity Substrates - Gonzalo Expósito-Domínguez; José Manuel Fernández-González; Pablo Padilla; Manuel Sierra-Castañer (International Journal of Antennas and Propagation)
Double layer and edge-location via techniques are combined for electromagnetic band gap (EBG) size reduction. The study of the required number of elements and their dimensions is carried out in order to suppress the surface wave propagation modes and consequently to reduce the mutual coupling between radiating elements in low-permittivity substrates. By applying these techniques, the size of the EBG mushroom is reduced by 30%; however, the bandwidth operation maintains its value, and these structures can be integrated between radiating elements in broad bandwidth antennas.